INOVASI PENGELOLAAN LIMBAH SEKAM PADI MENJADI ARANG BRIKET SEBAGAI SOLUSI ENERGI HIJAU DI DESA KARANGTANJUNG KARAWANG - Eri Widianto; Kardiman Kardiman; Farradina Choria Suci; Siswadi Siswadi; Rizal Hanifi; Najla Salsabila; Hilman Imadul Umam; Teguh Pambudi (Lembaga Penelitian dan Pengabdian kepada Masyarakat - Universitas Abdurachman Saleh Situbondo, 2025)
Karangtanjung Village in Karawang Regency produces a substantial amount of rice husk waste, yet its utilization remains limited, with most of it being disposed of through open burning. This Community Service Program aims to enhance the skills of the Sukamanah II Farmers Group in converting rice husk waste into charcoal briquettes through technical training and the implementation of appropriate technology. The effectiveness of the program was evaluated using pre-test and post-test instruments to assess participants’ knowledge improvement. The results indicate an increase of 27–35% in average scores after the training sessions. The effectiveness analysis using the Normalized Gain (N-Gain) method shows that most participants achieved moderate to high improvement, with N-Gain values ranging from 0.33 to 1.00. Approximately 30–40% of participants reached the high-effectiveness category (N-Gain > 0.7), while the rest fell into the moderate category. These findings confirm that the combination of theoretical introduction, demonstration, and hands-on practice is effective in improving participants’ technical understanding of briquette production. Beyond cognitive improvement, the program also produced tangible outputs, including a briquette press machine and standardized production SOP modules. Early impacts include reduced open burning, increased productivity in biomass utilization, and emerging initiatives to establish a village-level briquette business unit. Overall, this program contributes to strengthening circular economy practices and promoting green energy innovation based on agricultural waste.